Present Status and Long-Term Changes of Water Quality Characteristics in Heavily Polluted Mediterranean Lagoon, Lake Mariut, Egypt - H.H. Ali, Mohamed; Abdel-Satar, Amaal M.; El-Sherif M. Goher., Mohamed (IJRDO-Journal of Applied Science, 2017)
The present status, a long term change of water quality characteristics besidesmetal pollution load (Fe, Mn, Zn, Cu and Cd) in water of a heavily pollutedMediterranean Lake (Mariut Lake northwest of Egypt) were investigated. Waterquality characteristics varied in a wide range among the different basins. Dependingon collecting data; the agricultural and domestic sewage drained from Al-Qalaa Drainresponsible for the most drastic deterioration status in main basin of the lake.Meanwhile, Aquaculture Basin has the highest values of salinity and consequentlyboth major cations and anions. Ratio of N:P indicated of potential N limits onphytoplankton growth. Almost, the values of all studied metals are higher thanstandard permissible levels. The contamination index (Cd) revealed that the order ofpollution increasing as WB < SB < AQB < MB. PCA analyses showed that most ofnutrient salts associated with heavy metals were responsible for heavily pollutedzones. Cluster analyses showed that, main basin has the most polluted aspectsdepending on concentration of studying parameters followed by a moderate pollutedaquaculture basin then low polluted western and southern basins.